POLISH NECROPOLIS AS A TOURIST RESOURCE AND A FACTOR IN THE DEVELOPMENT OF UKRAINIAN-POLISH TOURISM AFTER THE WAR - SMYRNOV, Igor; LUBITSEVA, Olga (Bulletin of Taras Shevchenko National University of Kyiv, Geography, 2025)
The peculiarities of Polish necropolises as a tourist resource are revealed. Polish necropolises (both within modern Poland and beyond - in Ukraine, Lithuania, France) are an important tourist resource that can attract significant tourist flows. For Ukrainian tourists, it is fascinating from a historical, cultural and architectural point of view to get acquainted with the Polish cemeteries and graves that have been preserved today on the territory of Ukraine (in particular, in Lviv, Kyiv, Ivano-Frankivsk, Drohobych, Sambor, Fastov, Kamianets-Podilskyi, etc.), and to visit the relevant necropolises during visits to Poland, in particular, in Warsaw, Krakow, Zakopane, etc. The Orthodox Volsky cemetery in Warsaw is of particular interest to Ukrainian tourists, where one can see the graves of UNR figures and their relatives. At the same time, during the stay of Ukrainian tourists in such Polish cities as Szczecin, Wroclaw, Gdansk and others in the western and northern parts of Poland, questions from tourists about the locations and fate of old German cemeteries may be inconvenient for the Polish hosts. Ukrainian tourists should be informed about this during tours to the respective Polish cities. And for Polish tourists, a pleasant surprise can be the good preservation of Polish graves in Lviv (at the Lychakovsky Cemetery, including the recently restored Cemetery of Polish Eagles), Kyiv (Baikove Cemetery and the Polish Military Cemetery in Bykivnya), Kamianets-Podilskyi (monuments to Yuri Volodyevsky and Pope John Paul II, a commemorative plaque of the writer Henrik Sienkiewicz), etc. Therefore, the study of this issue is relevant and can contribute to improving the quality of tourist services for Ukrainians in Poland and Poles in Ukraine, in particular during the post-war recovery of the tourism industry in Ukraine.